2015
DOI: 10.1016/j.placenta.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Gestation age dependent transfer of human immunoglobulins across placenta in timed-pregnant guinea pigs

Abstract: IntroductionWhen administered during pregnancy, antibodies and other biologic drugs that contain the Fc part of the IgG molecule can traverse the placenta. Although it is generally accepted that the FcRn receptor mediates this process, gaps remain in our understanding of underlying details in humans and in common laboratory animal species.MethodsWe expanded our previous studies in timed-pregnant guinea pigs to both measure the transport of human (h) IgG at earlier gestation ages in vivo and evaluate FcRn funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…These results suggest that while ZIKV challenge in pregnant guinea pigs did not result in detectable viremia, a subclinical infection sufficient to elicit a robust antiviral antibody response did occur. Additionally, the observed accumulation of anti-ZIKV NS1 in fetal plasma was consistent with previous reports of the timing and kinetics of maternal to fetal transfer of IgG in both guinea pigs and humans [ 36 38 ].…”
Section: Resultssupporting
confidence: 91%
“…These results suggest that while ZIKV challenge in pregnant guinea pigs did not result in detectable viremia, a subclinical infection sufficient to elicit a robust antiviral antibody response did occur. Additionally, the observed accumulation of anti-ZIKV NS1 in fetal plasma was consistent with previous reports of the timing and kinetics of maternal to fetal transfer of IgG in both guinea pigs and humans [ 36 38 ].…”
Section: Resultssupporting
confidence: 91%
“…We found that the mean maternal concentrations trend progressively lower with increased gestation ( Figure 3(a) and supplemental Table S1) whereas the corresponding mean fetal concentrations progressively increase ( Figure 3(b) , and [ 21 ]). These two variables were negatively correlated ( Figure 3(f) ) and, after log transformation, the relationship was linear (Pearson correlation r = −0.60, p = 0.0008, confidence interval −0.80 to −0.29).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we showed that pregnant guinea pigs are an appropriate animal model for studying human antibody transfer during pregnancy [ 21 , 23 ]. The additional experimental data we present here enabled us to more precisely measure placental transfer and further demonstrate that this model recapitulates well the time course of the placental transfer of IgG in pregnant women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations